2009
DOI: 10.1007/s00586-009-1201-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and clinical meaning of long-term degenerative changes after lumbar discectomy visualized on imaging tests

Abstract: The aim of this retrospective controlled study was to evaluate radiographic degeneration in the lumbar spine of patients who had undergone lumbar discectomy minimum 21 years earlier and its clinical meaning. Indeed, no previous investigation on degenerative changes occurring after lumbar discectomy with a comparable long follow-up has been published. The study participants consisted of 50 patients who had undergone discectomy for lumbar disc herniation. The mean length of follow-up was 25.3 ± 3.0 years. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 35 publications
0
33
1
Order By: Relevance
“…8,11,18,21 Other authors have proposed that back pain after an OLD is associated with disc degeneration as a result of disc space narrowing or endplate sclerosis. 13,15,16 Because it is difficult to establish whether specific radiological findings are associated with certain clinical outcomes, we wanted to determine which radiological findings may be associated with common clinical outcomes of an OLD. Moreover, to focus on the long-term effects of OLD for LDH on radiological and clinical outcomes, only patients treated with OLD who had been followed up for 10 years or longer were included in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,11,18,21 Other authors have proposed that back pain after an OLD is associated with disc degeneration as a result of disc space narrowing or endplate sclerosis. 13,15,16 Because it is difficult to establish whether specific radiological findings are associated with certain clinical outcomes, we wanted to determine which radiological findings may be associated with common clinical outcomes of an OLD. Moreover, to focus on the long-term effects of OLD for LDH on radiological and clinical outcomes, only patients treated with OLD who had been followed up for 10 years or longer were included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…2,8,11,13,18,21,23 Yorimitsu et al 23 reported a 25% loss of the disc height 10 years after a discectomy, and Barth et al…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were asked to answer questions regarding their satisfaction with the original operation and reoperation (if applicable). Satisfaction with the operation was expressed through a four-step incremental scale (0 = dissatisfied, 1 = low satisfaction, 2 = moderate satisfaction, 3 = complete satisfaction) [9]. A single author who was uninvolved in the patients' primary care and who was unaware of the questionnaire results performed all the clinical assessments.…”
Section: Study Populationmentioning
confidence: 99%
“…If it is decided to treat conservatively, then we must be certain that the patients are not off work whilst they recover. The paper by Mariconda et al [27] looks at the frequency and clinical significance of the long-term degenerative changes in the disc 10 years after discectomy. Although those who had had a disc operation had more disc space narrowing, facet arthritis and endplate changes than a control group, there was little clinical difference between them.…”
Section: Disc Herniationmentioning
confidence: 99%